Phosphorus addition increases stability and complexity of co-occurrence network of soil microbes in an artificial Leymus chinensis grassland - Zhou, Xiaoguo; Hu, Yutong; Li, Huijun; Sheng, Jiandong; Cheng, Junhui; Zhao, Tingting; Zhang, Yuanmei (Frontiers in Microbiology, 2024)
Understanding the response of cross-domain co-occurrence networks of soil microorganisms to phosphorus stability and the resulting impacts is critical in ecosystems, but the underlying mechanism is unclear in artificial grassland ecosystems. In this study, the effects of four phosphorus concentrations, P0 (0 kg P ha -1 ), P1 (15.3 kg P ha -1 ), P2 (30.6 kg P ha -1 ), and P3 (45.9 kg P ha -1 ), on the cross-domain co-occurrence network of bacteria and fungi were investigated in an artificial Leymus chinensis grassland in an arid region. The results of the present study showed that phosphorus addition significantly altered the stem number, biomass and plant height of the Leymus chinensis but had no significant effect on the soil bacterial or fungal alpha (ACE) diversity or beta diversity. The phosphorus treatments all increased the cross-domain co-occurrence network edge, node, proportion of positively correlated edges, edge density, average degree, proximity to centrality, and robustness and increased the complexity and stability of the bacterial-fungal cross-domain co-occurrence network after 3 years of continuous phosphorus addition.Among them, fungi (Ascomycota, Basidiomycota, Mortierellomycota and Glomeromycota) play important roles as keystone species in the co-occurrence network, and they are significantly associated with soil AN, AK and EC. Finally, the growth of Leymus chinensis was mainly due to the influence of the soil phosphorus content and AN. This study revealed the factors affecting the growth of Leymus chinense in artificial grasslands in arid areas and provided a theoretical basis for the construction of artificial grasslands.